Hyperspectral ground truth data for the detection of buried architectural remains - Themistocleous, Kyriacos; Papadavid, George; Hadjimitsis, Diofantos G.; Agapiou, Athos (My University, 2010)
The aim of the study is to validate hyperspectral ground data for the detection of buried architectural remains. For this reason spectro-radiometric measurements were taken from an archaeological area in Cyprus. Field spectro-radiometric measurements were undertaken from March to May of 2010. Spectro-radiometric measurements were taken over the previously detected magnetic anomalies using the GER 1500 spectroradiometer and they were found to be in a general agreement with the geophysical results. The results of the subsequent excavations which took place in the area verified partially the geophysical and spectro-radiometric measurements. However, the results obtained from the in-situ spectro-radiometric campaigns were found very useful for detecting spectral vegetation anomalies related with buried features. This is an issue which the authors will continue to investigate since it has proven that local conditions of the area, such as geology, is a key parameter for the detection of buried architectural remains
Keywords: Radiometry; Architecture; Geophysics